RESPON PENANAMAN PADI GOGO BERAS MERAH DENGAN KACANG-KACANGAN TERHADAP BERAT BERANGKASAN DAN BERAT KERING AKAR PADA KONDISI LENGAS TANAH DAN MEDIA TUMBUH BERBEDA - CATHARINA, THERESIA SUZANNA; MEIKAPASA, NI WAYAN PUTU; DETHAN, STEVANY HANALYNA (Universitas Mahasaraswati Mataram, 2020)
Red rice rice planted on dry land needs to get attention. Drought is an obstacle to increasing production on rainfed land and even irrigated fields in the dry season. What if planting is done together? it will be easier to plant by mixing legume and non-legume plants compared to blocking it apart in a mixed cropping. From the results and research, it can be concluded that: joint planting between brown upland rice and beans is obtained: the highest dry weight of straw on growing media is from Kuripan. The highest root length at giving 100% water to the growing media comes from rice plants in Kuripan. The highest dry weight of rice roots in the growing medium is from Kuripan. Kuripan also has the highest dry weight of rice roots from the growing media with 50% water supply and the greater leaf area on the growing media with 100% water supply is from Bayan